Program Estafet Buku Berkelanjutan - Rani, Inta Hartaningtyas; Jalih, Jara Hardiyanti; Widyowati, Lestari Adhi (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2022)
T Books have great usefulness in education beyond only imparting knowledge from teacher to student. However, for various reasons, many students struggle to acquire books for educational purposes. Students may find it challenging to get a copy of a required textbook, including, but not limited to, financial constraints and limited copies. The Book Relay Program, in conjunction with the Muhammadiyah Student Association (IMM), is one of the implementers of this program and is expected to be able to give a solution to this problem through its methodical and structured approach. During the first semester of 2022, this service was only made available at the Ciputat and Karawaci campuses of the Ahmad Dahlan Institute of Technology. Volunteering entails a few distinct phases, from first contact with an organization in need of support to delivering program-related materials to IMM to tracking the spread of book relay program information.